1979
DOI: 10.1111/j.1365-2818.1979.tb00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Junctions In Fanft‐Induced Carcinomas Of Rat Urinary Bladder In Tissue Culture: In Situ Thin‐Section, Freeze‐Fracture, And Scanning Electron Microscopy Studies

Abstract: This paper describes a set of simple methods for comparative light and electron microscopy studies on tissue cultured tumour cells derived from both noninvasive and invasive carcinogen-induced rat urinary bladder carcinomas. Cells are grown on Thermanox plastic coverslips and fixed in situ. Each plastic coverslip is then divided with scissors into four parts: the first is processed for light microscopy, the second for thin-section electron microscopy, the third for freeze-fracture electron microscopy, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1981
1981
1990
1990

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…The significance of this isolated finding remains to be established. The ultrastructure and numerical densities of cell junctions in experimental urinary bladder carcinomas in Fischer rats do not correlate with invasiveness (12), nor are consistent differences in cell junctions observed in tissue culture lines derived from noninvasive and invasive rat bladder tumors (154). This may not be incompatible with the findings in human bladder carcinomas, since tumor morphology in humans and in rats is significantly different.…”
Section: Adhesion Locomotion and Chemotaxis A Loss Of Intercellulacontrasting
confidence: 45%
“…The significance of this isolated finding remains to be established. The ultrastructure and numerical densities of cell junctions in experimental urinary bladder carcinomas in Fischer rats do not correlate with invasiveness (12), nor are consistent differences in cell junctions observed in tissue culture lines derived from noninvasive and invasive rat bladder tumors (154). This may not be incompatible with the findings in human bladder carcinomas, since tumor morphology in humans and in rats is significantly different.…”
Section: Adhesion Locomotion and Chemotaxis A Loss Of Intercellulacontrasting
confidence: 45%
“…Cohen et al [9] and Pauli et al [7] revealed that cultured tumor cells of the rat bladder showed filopodia, pleomorphic microvilli and blebs. As mentioned above, deeper cells were reported to have slender strands, filopodia or microvilli on the sur faces of bladder tumors or non-neoplastic bladder mu cosa in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Since Arai et al [2], Jacobs et al [3] and Hicks and Wakefield [4] reported that these surface features of luminal cells changed in the neoplastic condition in duced by chemical carcinogens, the luminal surface to pography of these cells has been the focus of early mor phological changes of carcinogenesis in the urinary blad der. Namely, pleomorphic microvilli are recognized on the luminal surface of the superficial cells in irreversible hyperplasia and transitional cell carcinoma of the mam malian urinary bladder instead of the reticular micro ridges or short uniform microvilli on the luminal surface of superficial cells in the non-neoplastic epithelium [2][3][4], However, TEM observations showed that the superfi cial cells and the deeper cells in the mammalian transi tional cell epithelium and in bladder tumors had micro villous cellular processes and that some of these micro villous cellular processes were interwoven with others of neighboring cells in vivo as interdigitations in the inter cellular spaces [7,8]. Despite these descriptions of the topography of the luminal surfaces of these tissues, there have not been many reports describing the surface fea tures of the deeper cells in mammalian bladder tumors or bladder mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of some specimens, the copper hats were covered with a thin film of specimen mounting medium made according to Pauli et al (1979) before mounting the inverted plastic square on to the hat. The frozen specimens were fractured, etched for 1 min at 173 K and replicated using a freeze-etch unit manufactured according to Elgsaeter (1978).…”
Section: Freeze-etch Electron Microscopymentioning
confidence: 99%